Latar Belakang Pengalaman Musikal dan Kemampuan Dasar Vokalia Mahasiswa Baru Program Studi Sendratasik FBSS Universitas Negeri Padang - Jagar Lumbantoruan (Fakultas Bahasa dan Seni UNP, 2009)
The aim of this paper is to get describe the relationship between the students’ background of musical experience and the basic competence of the new students’ vocal music at the art program (sendratasik) of FBSS UNP. It is hoped that this paper can contribute in term of enabling the students to match themselves with demand of vocal the music lessons Keywords: musical experience, ability, vocal